Procter & Gamble v/s Colgate - 2003 : an exercise in competitive dynamics - Dixit, Mukund R.; Karthik, D. ([London] : SAGE, 2016)
This exercise describes the competitive dynamics situation faced by two large companies, Colgate-Palmolive and Proctor and Gamble in the oral care business. Both of them introduced tooth whitening solutions and anticipated to sustain their competitive lead. P&G introduced its solution in August 2000 and Colgate followed it in September 2002. This was followed by another introduction by Colgate in April 2003. This intensified the competitive battle between the two companies. The participants are required to get into the shoes of either Colgate or P&G to think through a competitive strategy. The case provides information on the estimated demand for tooth whitening solutions, gains and losses of the two companies, R&D expenditure, and players in the oral hygiene market.
Originally Published in: Dixit, M. R., & Karthik, D. (2013). Procter & Gamble v/s Colgate - 2003: An Exercise in Competitive Dynamics. BP0362. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Procter & Gamble Company; Colgate & Company; New products -- Case studies; Competition -- Case studies; Oral hygiene products -- Technological innovations -- Case studies